Interpretasi Surah At-Takatsur Perspektif Tafsir Kontemporer dan Relevansinya terhadap Fenomena Flexing di Era Digital - Dwi Nova Ardani; Mardian Idris Harahap (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to analyze the interpretation of Surah At-Takāthur from the perspective of contemporary Qur’anic exegesis and its relevance to the phenomenon of flexing on social media. The research employs a qualitative method with a library research approach. Primary data were obtained from the Qur’an and major exegetical works, particularly Fi Zhilal al-Qur’an by Sayyid Qutb, Tafsir Al-Mishbah by M. Quraish Shihab, and Tafsir Al-Munir by Wahbah al-Zuhayli. The data were analyzed using a descriptive-analytical approach to explore the meaning of at-takāthur and its contextualization within contemporary digital society. The findings reveal that Surah At-Takāthur criticizes human tendencies to pursue wealth accumulation, social status, and public recognition as primary life goals. In the context of digital society, flexing can be understood as a modern manifestation of at-takāthur, as both are oriented toward prestige and social validation. Such practices potentially encourage consumerism, social envy, and attitudes of ostentation, self-admiration, and arrogance that contradict Islamic ethical values. Therefore, contemporary interpretations of Surah At-Takāthur provide an important framework for developing Islamic digital literacy that emphasizes modesty, social responsibility, and a balanced orientation between worldly achievements and the hereafter.